Gamma Dose Measuring for the Rice Sample in Slemani City Markets, Kurdistan Region – Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
In this study, the Radium-226, Thoruim-232 and Potassuim-40 in the selected fourteen types of rice samples were collected from local markets in Slemani city- Kurdistan region- Iraq. The concentrations were determined by using scintillation detector (NaI (Tl) -3x3). The results of the Radium-226, Thoruim-232, and Potassuim-40 specific activities in rice samples were ranged (0.55 – 5.7) Bq Kg-1, (0.6 – 4.66) BqKg-1 and (16.11 – 20.02) Bq Kg-1, respectively. The average value of the radium equivalent activity ( ) was below the average worldwide values as reported by UNSCEAR. The values of total annual effective dose ( ) of the rice samples, ranged from 64.66 to 355.62 . The value of each of Thailand- Kallasher and Slemany_ Banikhellan samples were (355.62, 344.38), which were higher than the average worldwide value 290  as reported by UNSCEAR. In general, the mean value was 196.20. Therefore, the studied samples are safe in term of radiological health hazards.